Intrahousehold Bargaining and Resource Allocation in Developing Countries - Doss, Cheryl (Oxford University Press on behalf of the World Bank, 2014)
Many key development outcomes depend on women s ability to negotiate favorable intrahousehold allocations of resources. Yet it has been difficult to clearly identify which policies can increase women's bargaining power and result in better outcomes. This paper reviews both the analytical frameworks and the empirical evidence on the importance of women's bargaining power. It argues that there is sufficient evidence from rigorous studies to conclude that women's bargaining power does affect outcomes. But in many specific instances, the quantitative evidence cannot rigorously identify causality. In these cases, a combination of quantitative and qualitative evidence may suggest policy levers. Taken together, there are sufficient data in place to support a greatly expanded focus on intrahousehold outcomes and bargaining power. Additional data at the individual level will allow for further and more detailed research. A growing literature supports the current conventional wisdom -- namely, that the patterns of evidence suggest that women s education, incomes, and assets all are important aspects of women s bargaining power.